Status of HIV-1 Proviral DNA with the Treatment of Polyphytochemical Molecules - DR.S.K.PRAKASH (International Journal of Pharma and Bio Sciences, 2010)
The use of Highly Active Anti Retroviral Therapy (HAART) in Human Immunodeficiency Virus (HIV) infected patients can often significantly reduce the viral RNA to undetectable levels in plasma in both adults and children. One of the current challenges in the suppression or eradication of HIV-1 proviral DNA in latently infected CD4 lymphocytes and other reservoirs, which can replenish and revive viral infection upon activation. The phytochemicals which are present in Medicinal Herbs have been reported to have anti-hiv properties. Some medicinal plants have been reported to have immunostimulant properties. The ideal antiviral drug regimen would be one that induces strong and persistent suppression of viral replication, gives prolonged immunologic and clinical benefits without toxicity, can be administered at frequent dosage intervals, is affordable and easy to store, and can thus benefit the greatest number of HIV infected people, including those in developing countries. A 30 year old female, a symptomatic HIV-1 positive patient was given with the polyherbal regimen containing anti-HIV properties, anti-viral properties and immunostimulant properties for about more than three years. The qualitative proviral DNA, quantitative RT-PCR, quantitative p24 antigen assay, qualitative antibody assays , CD4 cells enumeration, CD8 cells enumeration were done before the treatment, in-between the treatment, after the treatment. The results were observed, recorded and interpreted. During the treatment the viral load gradually declined and finally came to less than the detectable limit after the attainment of undetectable level of viral load the proviral DNA also vanished. The CD4 and CD8 cells gradually increased. The infectivity was tested in PBMC culture before and after the treatment. The infectivity was present before the treatment and absent after the treatment. From the interpretations of the data the treatment has the significant effect towards the HIV-1 proviral clearance.